Fungsi dan Peran Api dalam Seni dan Kehidupan Masyarakat Bali - I Gusti Ngurah Sudibya; Pande Made Sukerta; Sardono Waluyo Kusumo; Eko Supriyanto (PANGGUNG, 2018)
ABSTRACTFire is made up of three elements, such as heat, combustible materials and oxygen. A fire has heat and light. Fire is used in real life in various human life from cooking, to marriage and to burning dead bodies. Fire is available in space, on earth, and in oneself. Symbolically the fire is employed as a symbol of spirit, a sanctification, a destruction, enlightenment, heating temperatures, fire of romance, and fire of revenge. Overheated is possible when one ignores norms, ethics, and rules. Library studies, interviews, observations, and experiments are the methods used in this compilation. Fire both as symbol and text, functioned according to the capacity/role of each, both in and outside themselves, the use of it must be controlled for the harmony of the macrocosms and microcosms, when is the right time is to use small, medium and large fire, because all of them is important.Keywords: function, fire, symbol, harmonic.ABSTRAKApi terbentuk dari tiga elemen yakni, panas, bahan mudah terbakar dan oksigen. Api memiliki panas dan cahaya. Api digunakan dalam kehidupan manusia dari memasak, penerangan, perkawinan sampai pembakaran jenazah. Api terletak di angkasa, di bumi, dalam diri. Api dijadikan simbol semangat, penyucian, peleburan, pencerahan, api asmara, api dendam. Terjadi over heated/panas berlebih yang tidak lagi mengindahkan norma, etika, aturan. Studi kepustakaan, wawancara, observasi, dan percobaan merupakan metode yang digunakan dalam penyusunan ini. Seyogyanya api baik sebagai simbol maupun teks, difungsikan sesuai kapasitas/perannya masing-masing, baik dalam diri maupun diluar diri, semua itu harus dikendalikan penggunaannya, agar keharmonisan bhuana alit dan bhuana agung dapat terwujud, kapan menggunakan api kecil, sedang maupun besar, karena semuanya penting.Kata kunci: fungsi, api, simbol, harmonis.